Nitration of Methyl Eugenol Derived from Clove Oil - Sudarma, I.M.; Shofiati, A.; Darmayanti, M.G. (Asian Journal of Chemistry, 2019)
No report is available in literature for the nitration of methyl eugenol. The main goal of this work is to find an efficient method for the synthesis of 5-nitro-methyl eugenol. 5-Nitro-methyl eugenol is of considerable importance in the production of other fine chemicals such as 5-amino-methyl eugenol for further chemical synthesis and has also possible to enhance its biological properties and other applications. The methyl eugenol can be prepared from methylation of eugenol which can be isolated from clove oil. In an attempt to synthesize nitro-methyl eugenol in high yield, three different nitration methods of methyl eugenol have been applied. Method (a) gave 5.97 %, (b) 84.37 % and (c) 11.40 %. Method (b) using a nitrating consisting mixture of HNO3 and H2SO4 under mild condition has been found to give 5-nitro-methyl eugenol in good yield.